2015
DOI: 10.15835/nbha.43.2.10081
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Antioxidant Activity and Color of Hydroponic Tomato Fruits at Different Stages of Ripening

Abstract: This experiment was carried out in order to study the simultaneous effect of on-vine ripening and examined cultivars on fruit quality, color development and antioxidant content in two different types of tomatoes. 'Admiro' and 'Komet' (normal average fruit weight) and 'Cheramy' (cherry type) cultivars grown in hydroponic culture were used. Dry matter, soluble solids, titratable acidity, ascorbic acid, lycopene, β-carotene, total phenolic, total flavonoid content and hydrophilic antioxidant activity were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 7 publications
3
16
1
1
Order By: Relevance
“…As noted by these authors, the TPC found in commercially available tomato juices ranged from approximately 2.0 to 9.4 mg GAE/g dm. On the other hand, the concentration of polyphenols in the fresh, untreated juice was almost 30% and 40% higher than that found in hydroponically grown tomatoes [ 24 , 25 ]. However, as demonstrated in the literature, the plant genotype and growth conditions are key determinants of the nutritional quality of the obtained product [ 26 ].…”
Section: Resultsmentioning
confidence: 88%
“…As noted by these authors, the TPC found in commercially available tomato juices ranged from approximately 2.0 to 9.4 mg GAE/g dm. On the other hand, the concentration of polyphenols in the fresh, untreated juice was almost 30% and 40% higher than that found in hydroponically grown tomatoes [ 24 , 25 ]. However, as demonstrated in the literature, the plant genotype and growth conditions are key determinants of the nutritional quality of the obtained product [ 26 ].…”
Section: Resultsmentioning
confidence: 88%
“…Total carotenoids are one of the most important antioxidants found in strawberries. It is reported that increase in total carotenoids is enhanced with the process of photosynthesis [35]. e process of photosynthesis occurs mainly due to the presence of chlorophyll, and it has been reported that chlorophyll and carotenoids are positively correlated with each other.…”
Section: Effect Of Different Substrates On Quality Parameters Ofmentioning
confidence: 99%
“…Aronia berry has a significantly higher polyphenol and antioxidant content than most fruits and vegetables (Nour et al, 2015;Jakobek and Seruga, 2012;Pérez-Jiménez, 2010). Aronia berry total polyphenols range from 1.0 to 3.6 g/100 g fwb (Denev et al, 2018;Nour et al, 2015). The primary polyphenols in aronia berries include anthocyanins, proanthocyanidins, flavonols, and phenolic acids.…”
Section: Polyphenolsmentioning
confidence: 99%